REJEITOS DO COCO VERDE PARA COMPOSIÇÃO DE MATERIAIS UTILIZÁVEIS NO DESIGN DE PRODUTOS PARA A CONSTRUÇÃO CIVIL - PINHO, Matheus da Silva (2025)
One of the striking characteristics of urban centers is the high demographic density, a property that fits the description of the city of São Luís, Maranhão. This fact implies the consumption and disposal of both objects and artifacts proportional to the number of consumers. As it is a product intensely marketed in the municipality, the green coconut is a source of several adversities within the urban perimeter due to its popularity among the inhabitants. To contribute to the reduction of the impacts arising from the disposal of this waste in the urban environment, the research has as a general objective to understand the benefits that green coconut fiber generates when added to a cementitious matrix mixture. This research is characterized by its applied and explanatory nature as to the objectives, quantitative in relation to the approach, supporting its content in bibliographic, documentary and laboratory research. During this study, a control group, called the standard group (P), formed only by mortar, and two other groups that replace 2.4% (F2.4) and 2.51% (F2.51) of the cement weight with green coconut fiber, were created. These sample sets (P, F2.4 and F2.51) were examined by the following tests: Fourier Transform Infrared Spectroscopy (FTIR), Energy Dispersive Spectroscopy (EDS), Scanning Electron Microscopy (SEM), water absorption, compression and four-point bending. After FTIR and EDS, it was possible to understand the chemical composition of the samples without and with green coconut fiber. On the other hand, SEM differentiated the surface texture of the matrix to the dispersed phase of the created material. In the water absorption test, a reduction in the density of the F2.4 and F2.51 composites was observed in relation to the P group. It was found that the union of coconut fiber with the cementitious matrix can have positive impacts by reusing an object frequently discarded in the city of São Luís, which makes it possible to reduce the use of cement, dissolving its environmental impacts over time. It is possible to conclude that design can be an articulator of apparently unrelated elements, bringing together different areas to seek ways to understand and diagnose situations related to the conception, production, consumption and disposal of objects and/or artifacts.